Microdynamics of Turkey's Export Boom in the 2000s - Cebeci, Tolga; Fernandes, Ana M. (Wiley, 2015)
This paper examines the microdynamics behind the dramatic export boom experienced by Turkey during the 2000s. Using disaggregated exporter-level customs data covering the universe of export transactions for Turkey during the period 2002–11, we characterize firm-level dynamics in the export sector and we decompose export growth at the aggregate, sectoral and destination market levels to identify the role of firm turnover, destination turnover and product turnover. We show that year-to-year aggregate export growth is dominated by growth in continuous exporters, and for these, growth is dominated by exports to their continued destinations and of their continued products. However, the observed high degree of churning across firms, destinations and products accounts for a substantial part of Turkey's export growth over longer periods. The patterns of microdynamics of export growth are verified across sectors and across groups of destination markets with some exceptions regarding exports to new emerging markets where net exporter entry plays a more critical role for export growth over longer periods.